Critical Discourse Analysis in Applied Linguistics: A Methodological Review. (22nd December 2014) - Lin, Angel
Abstract : The critical turn arrived in the field of applied linguistics in the late 1990s and early 2000s, and the field has since witnessed a burgeoning body of literature drawing on a variety of analytical frameworks and methodological approaches that are loosely labeled as critical discourse analysis (CDA). A methodological review of the role of CDA in the field is thus timely both to provide signposts for researchers wishing to draw on CDA methods in applied linguistics research and to provide some theoretical and methodological resources to evaluate the rapidly growing body of CDA-oriented applied linguistics research. Unlike some methodological tools, such as corpus analytic tools that can be inserted into a diverse range of theoretical frameworks (e.g., positivist studies, interpretive studies, critical studies), CDA cannot be applied divorced from its paradigmatic theories, as it is closely related to a specific set of social theories about the nature of language, literacy, identity, social practice, and the social world. CDA methods thus cannot be applied without also a concomitant commitment to CDA's theoretical orientations. In this review, the theoretical commitments as well as the classic methods of CDA will first be discussed and then the major areas in which CDA researchers typically conduct their studies are outlined together with a review of the variety of methodological approaches used in these different areas. The strengths as well as the limitations of these approaches will be discussed with examples of recent studies using CDA in the field of applied linguistics. The article will conclude with some suggestions for future directions of CDA methodological development.